PENGARUH MODAL KERJA DAN BIAYA OPERASIONAL TERHADAP PROFIABILITAS (ROI) (STUDI KASUS PADA PT. PLN (PERSERO) APJ MAJALAYA PERIODE 2010-2016) - Aditya Achmad Fathony; Eka Mahardika (Fakultas Ekonomi UNIBBA, 2018)
This research was conducted in PT.PLN (Persero) APJ Majalaya. The purpose of this study is to find out the effect of working capital and operating expenses on profitability at PT.PLN (Persero) APJ Majalaya either simultaneously although partially. The method which is used in this research is descriptive method with a quantitative approach. To know the influence of operational cost on profitability and working capital used statistical tests. Statistical tests are used is the use of multiple regression, correlation coefficient, coefficient of determination and also using SPSS 20.0 for windows applications. From the calculation of multiple correlation (R) of 0,945 which means the magnitude of the relationship of working capital and operational expenses and on profitability has a strong relationship. Results F tabel value of 6,094. Because F count (0,945) < F tabel (6,094). Values are means that working capital and operating costs together (simultaneously) has not significant influence on profitability at PT.PLN (Persero) APJ Majalaya Company. lowered relationship between warking capital and operating cost on profitability at PT.PLN (Persero) APJ Majalayaby 35,3% and the remaining 64,7% is influenced by other factors.